2014
DOI: 10.1136/annrheumdis-2014-eular.5556
|View full text |Cite
|
Sign up to set email alerts
|

THU0310 Predictors of Therapeutic Success of Steroids Injection in the Carpal Tunnel Syndrome: A Retrospective Multivariate Analysis of A Multicenter Cohort

Abstract: Background Treatment of moderate to severe carpal tunnel syndrome includes the possibility of local steroid injections, however the treatment success rate and its duration are very variable. There is no study designed to predict if a local steroid injection will be success or not. Sometimes local steroids injections delays surgical procedures without solving patient symtoms. A marker capable to predict success of failure should be useful in terms of chosing best therapy for these patients. Objectives The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Another study retrospectively evaluated clinical outcomes after steroid injection in 166 wrists with moderate to severe carpal tunnel syndrome to determine predictors of improved Boston Carpal Tunnel Questionnaire scores at 3 months and found that therapeutic success highly correlated with power Doppler signal at diagnosis. 20 This agrees with findings from a prospective study of 40 wrists assessing response to treatment with ultrasonography and electrodiagnostic studies in which only power Doppler ultrasound had significant correlation with improvement in Boston Carpal Tunnel Questionnaire and visual analogue scale pain scores at 6 weeks. 35 In contrast, one study evaluated clinical outcomes using the Disabilities of the Arm, Shoulder and Hand instrument; the Boston Carpal Tunnel Questionnaire; and visual analogue scale pain and physician assessment questionnaires, finding no significant correlations with semiquantitatively graded power Doppler signals.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Another study retrospectively evaluated clinical outcomes after steroid injection in 166 wrists with moderate to severe carpal tunnel syndrome to determine predictors of improved Boston Carpal Tunnel Questionnaire scores at 3 months and found that therapeutic success highly correlated with power Doppler signal at diagnosis. 20 This agrees with findings from a prospective study of 40 wrists assessing response to treatment with ultrasonography and electrodiagnostic studies in which only power Doppler ultrasound had significant correlation with improvement in Boston Carpal Tunnel Questionnaire and visual analogue scale pain scores at 6 weeks. 35 In contrast, one study evaluated clinical outcomes using the Disabilities of the Arm, Shoulder and Hand instrument; the Boston Carpal Tunnel Questionnaire; and visual analogue scale pain and physician assessment questionnaires, finding no significant correlations with semiquantitatively graded power Doppler signals.…”
Section: Discussionsupporting
confidence: 89%
“…31,32,36 Some researchers looked at accuracy in detecting prognosis of treatment and patient satisfaction. 7,20,23,35 Biases Risks of biases were considered in the interpretation and applicability of results. Retrospective selection of patients in three studies 20,28,29 could lead to verification and detection biases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, attempts have been made to evaluate the role of carpal ultrasound in the diagnosis of CTS [7][8][9][10]. In all cases, the initiative to validate ultrasound as a diagnostic tool is justified by its greater availability and accessibility.…”
Section: Introductionmentioning
confidence: 99%